Stem cell-associated transcription factors in non-functioning pituitary neuroendocrine tumours - Øystese, Kristin Astrid; Olarescu, Nicoleta Cristina; Lindskog, Cecilia; Xheka, Fabjola; Berg-Johnsen, Jon; Berg , Jens Petter; Bollerslev, Jens; Casar-Borota, Olivera (Free Neuropathology, 2024)
Background: Cells with stem cell features have been described in pituitary neuroendocrine tumours (PitNETs). Transcription factors SOX2 and SOX9 are stem cell-associated markers while the pituitary progenitor marker PROP1 is involved in anterior pituitary development. We characterised the presence of these markers known to be present in the human pituitary in non-functioning (NF) PitNETs. Methods: We investigated the pituitary transcription factors SOX2, SOX9 and PROP1 by immunohistochemistry (IHC) (N = 125) and RT-qPCR (N = 78) in a retrospective cohort of clinically NF-PitNETs. The markers were scored based on the percentage of immunolabeled cells. IHC staining scores were compared to reintervention rates for the whole cohort, and to expression of FSH, LH or ER in gonadotroph NF-PitNETs. Results: Most tumours showed no or few cells positive for SOX2, SOX9 and PROP1. More patients with SOX2-negative tumours went through reintervention (40 % vs 19 %, p = 0.03). SOX2, SOX9 and PROP1 staining correlated positively to each other (SOX2 and SOX9 rs = 0.666, SOX2 and PROP1 rs = 0.704, SOX9 and PROP1 rs = 0.570, and p < 0.001 for all). In gonadotroph NF-PitNETs, staining for SOX2 and PROP1 was positively associated to FSHβ staining (p < 0.001 for both). Staining for SOX2, SOX9 and PROP1 was positively associated with gene expression of Estrogen Receptor 1 (ESR1) (p < 0.001, p = 0.004 and p < 0.001) and IHC staining for ERα (p = 0.001, p = 0.03 and p = 0.05, respectively). Conclusion: SOX2, SOX9 and PROP1 were present at low levels in NF-PitNETs. Absence of SOX2 staining was associated with a higher reintervention rate. The stem cell markers correlated positively with markers of gonadotroph differentiation in gonadotroph NF-PitNETs. SOX2 and SOX9 were frequently coexpressed and showed positivity in intratumoural cells with epithelial features, however without coexpression of pituitary transcription factors.